2018
DOI: 10.1016/j.worlddev.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Bad Karma or Discrimination? Male–Female Wage Gaps Among Salaried Workers in India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 29 publications
7
30
2
4
Order By: Relevance
“…Relevant studies that are necessary to set out the outset of the study are reported in this article. Avalanche of published literature can be witnessed on women development across the globe including: identifying the capabilities of women's leadership and sustainable development in Colombia (Barrios et al, 2020), exploring the relationship between female directorship and firm performance in France (Bennouri et al, 2018), gender inequality in assets ownership in Latin America (Deere et al, 2010), wage gaps of female-male among salaried workers in India (Deshpande et al, 2018;Lee & Wie, 2017;Menon & Rodgers, 2009), uncovered opportunities and barriers of female employment in sports in UK (Forsyth et al, 2019), women segregation in tourism employment in APEC region (Hutchings et al, 2020), women empowerment in East Africa (Miedema et al, 2018), women empowerment in Nepal (O'Hara & Clement, 2018), women asset ownership in rural south-east and north-east Nigeria (Oladokun et al, 2018), participation of Saudi women in development index (Omair et al, 2020), gender wage gap in Mexico (Popli, 2013), gender wage discrimination in Pakistan (Sabir & Aftab, 2007;Yasmin, 2009), gender wage inequality between 1992-2014 in Sri Lanka (Seneviratne, 2020), role of female directors and stock price in China (Shahab et al, 2020), women's social and financial empowerment in Pakistan (Tahir et al, 2018) and gender wage gap in Philippines (Zveglich Jr. et al, 2019). Bennouri et al (2018) examined the data of 394 French firms and affirmed that there is a positive relationship between female board directorship and firm performance; similar finding have been found by Nekhili & Gatfaoui (2013) and Peni (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant studies that are necessary to set out the outset of the study are reported in this article. Avalanche of published literature can be witnessed on women development across the globe including: identifying the capabilities of women's leadership and sustainable development in Colombia (Barrios et al, 2020), exploring the relationship between female directorship and firm performance in France (Bennouri et al, 2018), gender inequality in assets ownership in Latin America (Deere et al, 2010), wage gaps of female-male among salaried workers in India (Deshpande et al, 2018;Lee & Wie, 2017;Menon & Rodgers, 2009), uncovered opportunities and barriers of female employment in sports in UK (Forsyth et al, 2019), women segregation in tourism employment in APEC region (Hutchings et al, 2020), women empowerment in East Africa (Miedema et al, 2018), women empowerment in Nepal (O'Hara & Clement, 2018), women asset ownership in rural south-east and north-east Nigeria (Oladokun et al, 2018), participation of Saudi women in development index (Omair et al, 2020), gender wage gap in Mexico (Popli, 2013), gender wage discrimination in Pakistan (Sabir & Aftab, 2007;Yasmin, 2009), gender wage inequality between 1992-2014 in Sri Lanka (Seneviratne, 2020), role of female directors and stock price in China (Shahab et al, 2020), women's social and financial empowerment in Pakistan (Tahir et al, 2018) and gender wage gap in Philippines (Zveglich Jr. et al, 2019). Bennouri et al (2018) examined the data of 394 French firms and affirmed that there is a positive relationship between female board directorship and firm performance; similar finding have been found by Nekhili & Gatfaoui (2013) and Peni (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2019) and Ullah et al (2020) asserted that female board representation has positive impact on firm performance particularly for those firms who intend to be creative and innovative.del Carmen Triana et al (2019) argued that educational background of top management team and inter-organizational strategic alliance support for moderation between strategic change and senior management gender diversity. Deshpande et al (2018) found male-female wage discrimination among salaried workers in India wherein female are likely to be paid less. Forsyth et al (2019) identified barriers and opportunities of female employment in sports and bolstered that gender inequality is still need to be addressed in educational sports related settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Southeast Asian countries, trends and causes of gender wage differentials vary. Deshpande, Goel, and Khanna (2018) used nationally representative data from the Employment-Unemployment Surveys in 1990-2000 and 2009-2010 to explore gender wage gaps among regular wage workers in India. They found that the wage ratio of women to men decreased from 55% in 1999-2000 to 49% in 2009-2010, and the bulk of the gender wage gap was unexplained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Caste and gender are the major demographic variables controlled for. The presence of a substantial wage penalty for women has been demonstrated by Deshpande et al (2015), while Madheswaran and Singhari (2017) have shown that there exist significant wage penalties for lower castes in the Indian labour force. In terms of caste, the categories considered are those officially classified as Scheduled Castes (SC), Scheduled Tribes (ST), Other Backward Castes (OBC) and Others.…”
Section: Empirical Analysis: Worker Protection In Regular Wage Employmentioning
confidence: 99%